Preparation of Nanocomposite Based on Exfoliation of Montmorillonite in Acrylamide Thermosensitive Polymer. (17th March 2013) - Zabarjad Shiraz, Nader; Enferad, Elham; Monfared, Aazam; Mojarrad, Mohammad Ali
Abstract : Poly( N -isopropylacrylamide) (PNIPAM) was synthesized in the presence of AIBN as radical initiator. The structure of polymer was elucidated using IR, 1 H NMR, and 13 C NMR spectroscopies and TGA thermogram. Exfoliated nanocomposite based on thermosensitive polymer (PNIPAM) was prepared utilizing montmorillonite (MMT) by solution blending. Its dispersion characteristics were investigated using SEM, X-ray diffraction, and particle size analysis. XRD showed exfoliation of MMT in polymer matrix above lower critical solution temperature (LCST). SEM indicated that polymer chains were dispersed among the layers of MMT. Particle size analysis showed two distinctive regions at 311 (31/5%) and 1160 (68/5%) nm.